2020
DOI: 10.1159/000512319
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nasal Airway Stent Therapy for the Treatment of Mild-to-Moderate Obstructive Sleep Apnea Syndrome

Abstract: <b><i>Background:</i></b> Patients with obstructive sleep apnea syndrome (OSAS) experience excessive daytime sleepiness and insomnia and they are at risk of developing cardiovascular disease and stroke. Continuous positive airway pressure therapy could improve symptoms and decrease these risks; however, adherence is problematic. Although the oral appliance is another therapeutic option, patient satisfaction is limited and the effect of the nasal airway stent – a new device – remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…22 Ultimately 30% of patients were unable to complete the 1-month study period for Nastents in the Ohtsuka study. 15 Compliance with nasal dilators was approximately 60% at 6 months in Löth's study driven by a reported lack of benefit, poor fit, or discomfort. 23 At 5 years, compliance in the same patient population dropped to 21%.…”
Section: Limitations Of Nasal Appliancesmentioning
confidence: 98%
See 1 more Smart Citation
“…22 Ultimately 30% of patients were unable to complete the 1-month study period for Nastents in the Ohtsuka study. 15 Compliance with nasal dilators was approximately 60% at 6 months in Löth's study driven by a reported lack of benefit, poor fit, or discomfort. 23 At 5 years, compliance in the same patient population dropped to 21%.…”
Section: Limitations Of Nasal Appliancesmentioning
confidence: 98%
“…15 Ohtsuka also studied the Nastent in patients with mild to moderate OSA and found a significant improvement in AHI (from 12.7/h to 8.6/h), Respiratory Distress Index, Oxygen Desaturation Index, and snore volume at 1month. 16 AlaxoLito devices are an alternate nasopharyngeal stenting device made from braided thin nitinol wire. A single re-useable 6-inch device is available for $974.…”
Section: Endonasal Dilators (Ends)mentioning
confidence: 99%
“…Furthermore, nasopharyngeal stenting devices have been used, with some success, to address sleep-related velopharyngeal obstruction, the primary site of obstruction in the majority of OSA cases. 11 Again, this is another continuous positive airway pressure alternative that deserves further consideration.…”
mentioning
confidence: 99%